(untitled) (PerCursos, 2022)
The following paper starts by looking at the definition of certain programs within the scope of the UNESCO (United Nations Educational, Scientific and Cultural Organization), according to which a Geopark is described as a territory with defined boundaries and an area large enough to support local socioeconomic development. It must be stressed beforehand that bibliographic resources are scarce for the time being, as the very subject is new and still under construction The essential idea in this work dwells on the realization that the Caçapava Aspiring Geopark fulfills the criteria to become an actual geopark if one just looks into the potential of said territory to develop endogenously. The focus is on the sociospatial configuration, a category blending concepts such as geodiversity, sustainability, development, and territory. A relevant local factor is mutton production as being practised in a unique terrain as far as landscape, nature and human lore are concerned, thus ultimately turning mutton into a territorial mark as well as a terroir product: the brand of lamb meat. Actually, mutton can be, as this work aims to show – the starting point to combine theory and praxis, as it stands out as the most important and conspicuous trigger for local endogenous development in the Alto Camaquã region, where Caçapava Aspiring Geopark is located.